Refractional astigmatism prevalence and its relationship with grating acuity in children 2 to 36 months of age - Lipener, César [UNESP]; de Haro Munoz, Emilio [UNESP]; de Castro Moreira, José Belmiro [UNESP]; Berezovsky, Adriana [UNESP]; Salomão, Solange Rios [UNESP]; Ventura, Dora Fix (FapUNIFESP (SciELO), 2006)
Purpose: To evaluate refractional astigmatism prevalence and its relationship with grating acuity in a cohort of non-verbal children. Methods: 482 normal children, aged from 2 to 36 months, were submitted to ophthalmological examination. Fourteen subjects were excluded due to ocular disease and the sample remained with 468 subjects (936 eyes); 230 (49%) males e 238 (51%) females. Grating acuity was assessed binocularly and monocularly with Teller acuity cards. All children underwent eye examination including cycloplegic retinoscopy and fundus by indirect ophthalmoscopy. Results: Astigmatism was found in 222 (47.43%) of the children, with the hyperopic and with the rule types most frequently found in all ages. Concerning magnitude, this condition was equal or greater than 1.00 cylindric diopter in 24.35% of the children; equal or greater than 2.00 cylindric diopter in 5.55%; lower than 1.00 in 26.92% and between 1.00 and 2.00 in 18.73%. Grating acuity was normal in 219 of the subjects, despite magnitude, type and orientation of astigmatism. Conclusion: Visual acuity assessed by the acuity card procedure was not influenced by astigmatism.
Prevalência de astigmatismo refracional e sua relação com a acuidade visual de resolução em crianças de 2 a 36 meses
Keywords: Astigmatism; Child; Prevalence; Visual acuity/methods